Adolescent mental health: are we doing enough?. (29th September 2015) - Mills, S; Mohan, A; Sahi, S
Abstract : Aim: The lack of service provision for children aged 16–18 with mental health problems is well established.1 Frequently leading to a poorly co-ordinated service in which these children fall through gaps left between paediatric and adult services sometimes causing inadequate care and follow up. Using national guidelines we evaluated whether the mental health assessment and management of self harm in adolescents under 18 years was in line with the standards dictated both nationally and locally. Methods: Data were collected retrospectively on all children attending the paediatric accident and emergency (A&E) in a 12-month window (Jan 2006 to Dec 2006) with the presenting complaint of self harm. A total of 54 patients were identified. Results: 23% male. 28 assessed by paediatrics, 16 needed immediate psychiatric assessment (30%). 56% were admitted. Nine of the patients presented within office hours. 29 patients aged 16–18. Of which: Three admitted to the paediatric ward, five admitted by the adult medical team, four left before treatment. Of the 11 patients assessed and discharged by A&E, seven had follow up arranged, three left without any follow up and one patient self discharged. Conclusion: Current recommendations are that admission to hospital after an episode or suspected episode of self harm, is desirable, under the overall care of a paediatrician.2 3 Young people of less than 16 would be most suited to paediatric ward or if available an adolescent unit. Young people between 16 and 18, if appropriate, can be admitted to adult services. It appears the majority of patients are being discharged home after A&E assessment. 83% patients presented out of hours meaning robust management pathways and referral routes should be in place to ensure correct management and follow up takes place. 11% left hospital without being assessed. In an attempt to prevent those in need leaving hospital without the required attention a mental health assessment tool is now used in A&E triage. Awareness should be raised among A&E staff for the management of this vulnerable group. Re-audit is planned for 2010.